Efficacy of Annona muricata (Soursop) Leaf Extracts on Locust Mortality: An Environmentally Friendly Approach to Pest Control in Pterocarpus indicus Cultivation: Khasiat Ekstrak Daun Annona muricata (Sirsak) Terhadap Kematian Belalang: Pendekatan Ramah Lingkungan Pengendalian Hama Pada Budidaya Pterocarpus indicus - Rindiyani Bazargan; Fransina Latumahina; Cornelia Wattimena (Universitas Muhammadiyah Sidoarjo, 2023)
This research aimed to examine the effectiveness of different concentrations of soursop (Annona muricata) leaf extracts on locust mortality in Pterocarpus indicus plants. A completely randomized design was used involving various concentrations of soursop leaf extracts (0, 250g, 500g, 750g, 1000g per liter of water), each tested in triplicate. Each experiment included 20 locusts, with a total of 300 locusts required for all tests. The soursop leaf extract was prepared by blending fresh leaves with water and filtering, then applied using a sprayer at six-hour intervals. Data analysis was performed using the analysis of variance (ANOVA) method. The results demonstrated that soursop leaf extract significantly affected locust mortality across all concentrations, with even the lowest concentration (250g/L) proving effective. These findings suggest that soursop leaf extract represents a potent, natural biopesticide for locust control, underlining its importance for farmers and offering a sustainable and environmentally friendly solution to pest management in Pterocarpus indicus cultivation. Highlights: Soursop (Annona muricata) leaf extract demonstrates significant effectiveness as a biopesticide against locusts in Pterocarpus indicus plants. Even the lowest concentration (250g/L) of soursop leaf extract can effectively control locust populations, indicating a high potency. The use of soursop leaf extract as a biopesticide offers a sustainable, environmentally friendly approach to pest management in agricultural settings. Keywords: Annona muricata, Soursop Leaf Extract, Biopesticide, Locust Mortality, Pterocarpus indicus Cultivation.